Anda di halaman 1dari 4

# Penyelesaian:

## Fungsi Permintaan → Qd=64−8 P−2 P2

Fungsi Penawaran → Qs=10 P+5 P 2

Qd = Qs
64−8 P−2 P2=10 P+5 P2

## 64−18 P−7 P2=0

−7 P2−18 P+64=0

a = -7 b = -18 c = 64
−(−18 ) ± √ ( −18 2) −4 (−7 ×64 )
P1,2=
2 (−7 )

18 ± √ 324+ 1.792
P1,2=
−14
18 ± √ 2.116
P1,2=
−14
18 ± 46
P1,2=
−14

18+46
P 1=
−14
64 8 4
P 1= =−4 =−4
−14 14 7
18−46 −28
P 2= = =2
−14 −14

## Nilai P=2 disubstitusikan ke:

Q=10 P+5 P2
2
Q=10 ( 2 ) +5 ( 2 )
Q=20+ 20
Q=40

## Jadi, P=2 dan Q=40 (C)

Penyelesaian:
Fungsi permintaan → PQ +12 P+6 Q−97
Fungsi Penawaran → P−Q=6→ P=6 +Q

P Q+ 12 P+6 Q−97=0
( 6+Q ) Q+12 ( 6+Q ) +6 Q−97=0

## 6 Q+Q2 +72+12Q+6 Q−97=0

Q2 +24 Q−25=0

a=1 b = 24 c = -25
−24 ± √ ( 2 4 2) −4 (1 ×−25)
Q 1,2=
2(1)

−24 ± √ 576+100
Q1,2=
2
−24 ± √ 676
Q1,2=
2
−24 ± 26
Q 1,2=
2
−24+ 26 2
Q 1= = =1
2 2
−24−26 −50
Q 2= = =−25
2 2

P=6+Q=6+ 1=7

## Jadi, P=7 dan Q=1 (C)

Penyelesaian:
Fungsi permintaan → 2Q2 + P=9→ Pd =−2 Q2+ 9
Fungsi Penawaran → Q2+5 Q−P=−1 → P s=Q2 +5 Q+ 1

Pd = Ps
−2 Q2+ 9=Q2 +5 Q+1
−2 Q 2−Q 2−5 Q+9−1=0

−3 Q 2−5 Q+8=0

a = -3 b = -5 c=8
−(−5 ) ± √( −52 )−4 (−3 ×8 )
Q1,2=
2 (−3 )

5 ± √ 25+ 96
Q1,2=
−6
5 ± √121
Q1,2=
−6
5 ±11
Q1,2=
−6
5+11 16 4
Q 1= = =−2
−6 −6 6
5−11 −6
Q 2= = =1
−6 −6

P=−2Q2 +9
2
P=−2 ( 1 ) +9=7